Effects of Neuromuscular Electrical Stimulation (NMES) Plus Upper Cervical Spine Mobilization on Forward Head Posture and Swallowing Function in Stroke Patients with Dysphagia - Jeon, Yung Hyun (Brain Sci, 2020)
After a stroke, forward head posture occurs, resulting in swallowing dysfunction. Neuromuscular electrical stimulation (NMES) combined with upper cervical spine mobilization has demonstrated enhanced recovery of the swallowing function in stroke patients. This study investigated the therapeutic effects of NMES in conjunction with upper cervical mobilization in stroke patients with dysphagia. Thirty-four stroke patients were recruited (in a randomized controlled clinical trial) and divided into an experimental group (n = 17; NMES plus upper cervical spine mobilization) and a control group (n = 17; NMES plus sham mobilization). Forward head posture was measured by craniocervical flexion test (CCFT) and craniovertebral angle (CVA). Swallowing function was measured by variations in video fluoroscopic dysphagia scale (VDS) and penetration–aspiration scale (PAS) scores using the video fluoroscopic swallowing study (VFSS). All measurements were done at baseline and after four weeks of NMES plus mobilization. A significant increase was observed in CCFT, CVA, VDS (total VDS score, oral stage score, pharyngeal stage score), and PAS score in all variations in the experimental group. The CCFT, CVA, pharyngeal stage score, total VDS, and PAS score were significantly higher in the experimental group when compared to the control group. NMES plus upper cervical spine mobilization can be regarded as a promising method to improve swallowing function and forward head posture changes in stroke patients with dysphagia.